ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA BERDASARKAN TIPE KEPRIBADIAN LITTAUER - Stevie Flooryana; Nora Susilowaty (LPPM Universitas Advent Indonesia, 2022)
This study discusses the most dominant personality types at low, medium, and high levels of ability in mathematical problems and to describe students' problem-solving abilities in solving mathematical problems in SPLTV material based on the type appropriate to Littauer. This type of research is a descriptive study of qualitative research. The subjects in this study were 12 students from class X MIA 2 and X MIA 3 SMA Negeri 1 Parongpong. Data collection in the form of written tests and interviews. The results showed the most dominant personality type for each level of mathematical ability is phlegmatic. At a high level of mathematical ability, most of each type of student's ability can do every step of solving Polya problems well. At the moderate level of mathematical ability, each student's personality type can question the problem well, most students of each personality type have not been able to make a complete problem-solving plan, and are not careful in working on the problem, at the last stage of each type of student can be seen again his work At a low level of ability, students of each personality type are not able to make problemsolving plans well and correct the difficulty of solving problems, at the installation check only students with sanguine and choleric personality types need to return to work.